“Money Doesn’t Like Noise”: Akufo Addo’s Pathos from A Metadiscoursal Perspective - Emmanuel Kyei; Thomas Oduro Kwarteng; Wilson Awiah Jujugenia; Salomey Horsu; Dora Essah-Ntiful; Michael Kwame Appiah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Politicians create a political persona with their audience in mind, and their speeches are crafted to involve receivers in a promising future. They intentionally create a stream of ideas to engage the audience and arouse their emotions to make affective appeals. Using the frameworks of Hyland's Model of Metadiscourse and Aristotle's Rhetorical Persuasion Theory, the present study analysed Akufo Addo's address to the nation on October 30, 2022, when the country was facing economic difficulties. The study found that attitude markers, self-mentions, reader pronouns, and directives of metadiscourse markers are persuasively used in the data. The study concludes that Akufo Addo relied heavily on these metadiscourse markers to draw on pathos appeals, harmonise with the audience, and achieve the purpose of persuasion in the address. The findings of the study have implications for reflections on language and politics.